Methodological Rigors in Medical Journals from Developing Countries: An Appraisal of the Scenario in Asia (Nepal Journal of Epidemiology, 2011)
Several medical journals in developing countries are found to have methodological rigor when compared to those from developed European countries, which may contribute to the reasoning that research from Asian region is ‘fraudulent research’. It is very easy to find out whether the research is fraudulent or not by the critical review of the research article by the expert editors. It is sincerely recommended and encouraged by the Managing editor and Author that the contributing researchers follow a diligent and systematic pattern in conducting and presenting their studies. This will not only lead to improved quality of research but will also enhance and augment the quality of Asian journals and thus, contribute meaningfully to the progress of research and improvement of medical care in developing countries.DOI: http://dx.doi.org/10.3126/nje.v1i5.6151 Nepal Journal of Epidemiology 2011;1 (5):141-43